Novel thermally and mechanically stable hydrogel for enzyme immobilization of penicillin G acylase via covalent technique - Elnashar, Magdy; Yassin, M.; Kahil, T. (John Wiley and Sons Inc, 2008)
?-Carrageenan hydrogel crosslinked with protonated polyethyleneimine (PEI+) and glutaraldehyde (GA) was prepared and evaluated as a novel biocatalytic support for covalent immobilization of penicillin G acylase (PGA). The method of modification of the carrageenan biopolymer is clearly illustrated using a schematic diagram and was verified by FTIR, elemental analysis, DSC, and INSTRON using the compression mode. Results showed that the gels' mechanical strength was greatly enhanced from 3.9 kg/cm2 to 16.8 kg/cm 2 with an outstanding improvement in the gels thermal stability. It was proven that, the control gels were completely dissolved at 35°C, whereas the modified gels remained intact at 90°C. The DSC thermogram revealed a shift in the endothermic band of water from 62 to 93°C showing more gel-crosslinking. FTIR revealed the presence of the new functionality, aldehydic carbonyl group, at 1710 cm-1 for covalent PGA immobilization. PGA was successfully immobilized as a model industrial enzyme retaining 71% of its activity. The enzyme loading increased from 2.2 U/g (control gel) to 10 U/g using the covalent technique. The operational stability showed no loss of activity after 20 cycles. The present support could be a good candidate for the immobilization of industrial enzymes rich in amino groups, especially the thermophilic ones. © 2008 Wiley Periodicals, Inc.